Perancangan Rental Office Kota Summarecon Bekasi Dengan Pendekatan Arsitektur Bioklimatik - Purnama Sakhrial Pradini; Trias Pamungkas (DPPM Universitas Pelita Bangsa, 2022)
Bekasi City is the 4th largest city by population in Indonesia. With its location closest to Jakarta, Bekasi City seems to be the main gate to enter Jakarta from the east which is rapidly growing with business and industry. This has implications for the economic growth of Bekasi City which is better than other areas around Jakarta. Bekasi City is also an industrial and business city, as evidenced by the presence of various national and international giant companies. Various strategic plans have also been presented and continue to be developed in Bekasi City. These various strategic plans have stimulated the private sector and the state to compete to invest in Bekasi City. In line with the rapid economic growth of Bekasi City as well as the development of new infrastructure and transportation which in the end was able to attract investors to invest their capital. This has an impact on the increasing demand for office space with a strategic location and various ease of access in it. Furthermore, in running the business wheel of a company, it is deemed necessary to have a centralized place/area where carrying out business activities can be carried out easily and efficiently. Presenting an ideal office space with a different architectural concept is needed to be able to provide maximum results for the company & comfort for all employees. Keywords: Bekasi City, Office Rental, Office Building, Bioclimatic Architecture, Business Center